Diseño de un sistema contable agrícola en la Florícola Wilson Geovanny Toaquiza Toaquiza, Ubicado en la Provincia de Cotopaxi, Cantón Latacunga, Parroquia San Buenaventura, período segundo semestre 2022 - Callatasig Chisaguano, Elvia Marlene (2024)
The flower business sector refers to the industry dedicated to the cultivation, production and marketing of flowers. This area of commerce faces challenges related to global competition, production costs, internal management of adequate accounting, among others. The main problem found within the flower industry is the lack of knowledge of an accounting system, which has caused unnecessary financial losses. The objective of the project is to design an Agricultural Accounting System in the Florícola “Wilson Geovanny Toaquiza Toaquiza” in the Province of Cotopaxi based on the data of the second half of the period 2022. Its quantitative approach and field research allowed obtaining data directly from the stakeholders. In addition, the interview technique was applied to collect information provided by the owner manager and head of the cultivation and post-harvest area. The results obtained when calculating the unit and total costs reflect a total of 0.18 cents per stem, with a 70% profit obtained as a retail price of 0.31 cents, which is the real cost of the rose production. Accounting standards such as: Nic 41 and IFRS for SMEs section 34 were applied, which permitted maintaining a correct presentation of the Financial Statements for adequate decision making. Therefore, the Florícola is recommended to maintain an efficient accounting system designed to provide a solid foundation in future financial management.